Application of Innovative Teaching Methods in English Lessons - Shavkatovna, Sharipova Dilnoza; Gulomovna, Qutliyeva Muhayyo (International Journal on Integrated Education, 2023)
This article discusses the issue of improving the effectiveness of teaching English in non-linguistic universities. It also describes innovative teaching methods and approaches in English. The possibilities of expanding the competences of professors and teachers in the field of modern teaching methods are highlighted in order to identify the key components necessary for the implementation of this model of teaching students a foreign language in a university.